2022
DOI: 10.1002/cam4.4892
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive global collaboration in the care of 1182 pediatric oncology patients over 12 years: The Iraqi–Italian experience

Abstract: Background Iraq's health care system has gradually declined after several decades of wars, terrorism, and UN economic sanctions. The Oncology Unit at Children's Welfare Teaching Hospital (CWTH) in Baghdad was lacking basic facilities and support. To address this shortcoming, a humanitarian and educational partnership was established between CWTH and Sapienza University of Rome (SUR). Methods We investigated the outcomes of 80 online and 16 onsite educational sessions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The authors of this review concluded that more research is needed to determine the efficacy of implementing the more widespread use of telemedicine for hematological conditions. We believe that the results presented in this manuscript add some more arguments speaking in favor of the utility of telemedicine in the field of pediatric oncology and hematology [13][14][15].…”
Section: Discussionmentioning
confidence: 63%
“…The authors of this review concluded that more research is needed to determine the efficacy of implementing the more widespread use of telemedicine for hematological conditions. We believe that the results presented in this manuscript add some more arguments speaking in favor of the utility of telemedicine in the field of pediatric oncology and hematology [13][14][15].…”
Section: Discussionmentioning
confidence: 63%
“…Al-Jadiry et al. reported significant improvements in diagnoses and management of pediatric cancer in Iraq through a partnership with Sapienza University of Rome, which included teleconsultations and pathology reviews ( 13 ). Similarly, Qaddoumi and Bouffet found that e-mail exchanges enhanced a neuro-oncology twinning program between Jordan and Canada, facilitating communication and collaboration ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar efforts within lower middle-income countries (LMICs) are often limited to twinning initiatives between one LMIC center and an HIC center, that typically utilize videoconferencing with a focus on specific subspecialty case discussions. [6][7][8][9][10][11][12] Such initiatives have been successful in developing local expertise, but their reach is limited to the institution participating in the twinning, which is usually a reference center that has reasonable resources.…”
Section: Discussionmentioning
confidence: 99%
“…Videoconferencing among regional oncology networks has been mostly reported within high‐income countries (HICs), 4,5 and is associated with multiple benefits, including enhanced care coordination, optimization of treatment plans, and education of practitioners. Similar efforts within lower middle‐income countries (LMICs) are often limited to twinning initiatives between one LMIC center and an HIC center, that typically utilize videoconferencing with a focus on specific subspecialty case discussions 6–12 . Such initiatives have been successful in developing local expertise, but their reach is limited to the institution participating in the twinning, which is usually a reference center that has reasonable resources.…”
Section: Discussionmentioning
confidence: 99%